A nationwide outbreak of listeriosis associated with cold-cuts, Sweden 2013-2014. Issue 1 (1st January 2017) - Dahl, Viktor; Sundqvist, Lena; Hedenström, Ingela; Löfdahl, Margareta; Alm, Erik; Ringberg, Håkan; Lindblad, Mats; Wallensten, Anders; Thisted Lambertz, Susanne; Jernberg, Cecilia
ABSTRACT: In January 2014, the Public Health Agency of Sweden noticed an increase in listeriosis cases. Isolates from 10 cases had identical pulsed field gel electrophoresis (PFGE) profiles, suggesting a common source. We investigated the outbreak to identify the source and stop transmission. We looked for cases in 2013–2014 and also compared cases notified after February 2014 to randomly selected controls. We surveyed food items consumed two weeks prior to symptom onset. Listeria monocytogenes isolates found by food producers were PFGE-typed. Patient and food isolates with the outbreak PFGE profile were whole-genome sequenced and 51 cases with identical PFGE profile were identified; 12/20 cases and 108/186 controls responded to the survey. All cases were exposed to cold-cuts, compared with 72% of controls ( p = 0.034). Five isolates of L. monocytogenes with the outbreak PFGE profile were found in cold-cuts from a food producer which stopped production in February 2014, but cases appeared until October 2014. Whole-genome sequencing showed that cold-cut and patient isolates differed by eight single nucleotide polymorphisms. Three patient isolates differed more and were probably not part of the outbreak. Epidemiological and microbiological results indicated cold-cuts as a possible source of the outbreak.